Bananas Muli as a product fruit leather through using microwave and oven dryers - Dessy Agustina Sari; Nurcahyo Widyodaru Saputro; Azafilmi Hakiim; Sukanta (Journal of Sustainable Engineering: Proceedings Series, 2019)
Post-harvest processing of bananas Muli local Karawang – Loji area became a research study on a breakthrough the kind of food products. Previously, this fruit only sold to consumers in the roadside, and the rest was thrown away or not utilized. Users prefer to consume directly and fresh. After that, its medium size with a diameter 3 to 4 cm caused this raw material did not display to be a selling outcome such as “sale” or chips. Bananas Muli has never received further food processing compared to other types of bananas (such as bananas Kepok, bananas Raja, bananas Tanduk, bananas Ambon, and others). The term of fruit leather gave the development and novelty for product fruit categories in the form of sheets. Furthermore, the process that occurred was decreasing water content used microwave and oven dryers, then temperature range between 60-80oC with constant sample thickness in three suitable stabilizers. Utilization of oven dryers to produce banana leather products without stabilizers was more likely to choose a temperature of 70oC as the best condition for decreasing water content in the ingredients. Meanwhile, the use of microwaves was able to produce electromagnetic waves and caused collisions between molecules owned by the sample. The results indicated a positive effect. Carrageenan and starch were more capable of binding the water molecules. This way helped the process of reducing water content much faster from the surface (free water) to the area in the sample (water bound to the equilibrium water content). This research resulted in a decrease in water content in the example by 10,5701-12,8639% within 3 hours of the drying process at the optimum conditions